Factors contributing to Volunteer Smartphone Patrol app adoption in community policing / Ghazila Ghazi, Wan Hartini Wan Zainodin and Azizul Halim Yahya - Ghazi, Ghazila; Wan Zainodin, Wan Hartini; Yahya, Azizul Halim (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Social media platforms are becoming increasingly vital for businesses and non-profits alike. These advantages should translate wellfor police departments' use of social media. Even though many police departments have widely used social media in criminal investigations, many still could not adopt it effectively as it does not provide an exclusive platform for engagement and interaction between the citizens and the police. Meanwhile, the advancement of technology, particularly in digital media, has improved relations between police and citizens by incorporating people into policing activities through Community Policing (CP) mobile applications. Malaysia was not left behind in adopting the CP mobile application as it has its own Volunteer Smartphone Patrol (VSP) application supporting community policing activities, especially crime prevention. The engagement and interaction between citizens and police through VSP for crime prevention has assisted the transitionfrom traditional policing to CP more effectively. This study aims to discover the factors contributing to the VSP app adoption by citizens in community policing. Using a case study design, salient discoveries were obtained through in-depth interviews with 9 VSP users in Klang Valley. The NVivo 12.0 software was used in the process of open, axial and selective coding. The thematic analysis was used to analyse the data. This study found that the factors contributing to the VSP app adoption by citizens in community policing are practicality, responsiveness, surveillance, and security.